Measurement of Ejection Fraction by Cardiac Magnetic Resonance Imaging and Echocardiography to Monitor Doxorubicin-Induced Cardiotoxicity - Tak, Tahir; Jaekel, Camilla M.; Gharacholou, Shahyar M.; Dworak, Marshall W.; Marshall, Scott A. (International Journal of Angiology, 2020)
Doxorubicin is a standard treatment option for breast cancer, lymphoma, and leukemia, but its benefits are limited by its potential for cardiotoxicity. The primary objective of this study was to compare cardiac magnetic resonance imaging (CMRI) versus echocardiography (ECHO) to detect a reduction in left ventricular ejection function, suggestive of doxorubicin cardiotoxicity. We studied eligible patients who were 18 years or older, who had breast cancer or lymphoma, and who were offered treatment with doxorubicin with curative intent dosing of 240 to 300 mg/m2 body surface area between March 1, 2009 and October 31, 2013. Patients underwent baseline CMRI and ECHO. Both imaging studies were repeated after four cycles of treatment. Ejection fraction (EF) calculated by both methods was compared and analyzed with the inferential statistical Student's t test. Twenty-eight eligible patients were enrolled. Two patients stopped participating in the study before undergoing baseline CMRI; 26 patients underwent baseline ECHO and CMRI. Eight of those 26 patients declined posttreatment studies, so the final study population was 18 patients. There was a significant difference in EF pre- and posttreatment in the CMRI group (p = 0.009) versus the ECHO group that showed no significant differences in EF (p = NS). It appears that CMRI is superior to ECHO for detecting doxorubicin-induced reductions in cardiac systolic function. However, ECHO is less expensive and more convenient for patients because of its noninvasive character and bedside practicality. A larger study is needed to confirm these findings.
Keywords: breast cancer; cardiac imaging; cardiac MRI; cardiotoxicity; doxorubicin; echocardiography; lymphoma